Characteristics of silicon-based Sagnac optical switches using magneto-optical micro-ring array. Issue 1 (2nd January 2018) - Ni, Shuang; Wu, Baojian; Liu, Yawen
ABSTRACT: The miniaturization and integration of optical switches are necessary for photonic switching networks and the utilization of magneto optical effects is a promising candidate. We propose a Sagnac optical switch chip based on the principle of nonreciprocal phase shift (NPS) of the magneto-optical (MO) micro-ring (MOMR) array, composed of SiO2 /Si/Ce:YIG/SGGG. The MO switching function is realized by controlling the drive current in the snake-like metal microstrip circuit layered on the MOMRs. The transmission characteristics of the Sagnac MO switch chip dependent on magnetization intensity, waveguide coupling coefficient and waveguide loss are simulated. By optimizing the coupling coefficients, we design an MO switch using two serial MOMRs with a circumference of 38.37 μm, and the 3dB bandwidth and the extinction ratio are respectively up to 1.6 nm and 50dB for the waveguide loss coefficient of . And the switching magnetization can be further reduced by increasing the number of parallel MOMRs. The frequency response of the MO Sagnac switch is analyzed as well.